An open-label pilot study to evaluate the efficacy and safety of BC caps for women with abnormal vaginal discharge due to microbial infections: case series - Vikram, Baburao; Rawal, Neetu; Gupta, Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Herbal therapeutics advancement demand in management of abdominal vaginal discharge is increasing in women as it serves as an important housekeeping function in the reproductive system. This case series study evaluates the safety and effectiveness of birth control contraceptives capsules (BC caps) in women suffering from abnormal vaginal discharge. We conducted an open label interventional study of 15 female patients with in the age of 18-45 years (mean 33.7 years) with a history of abnormal vaginal discharge. Patients were asked to administer two BC caps (neem seed oil) capsule of 500 mg manually to vagina daily at night for 15 days followed by treatment assessment as per each schedule visit. Primary outcome includes change in microbiological parameters. Secondary outcomes included monitoring of adverse event (AE) and serious adverse event (SAE), changes in clinician’s assessment of symptoms and change in Subject’s global assessment of symptoms. The study showed the 93.33% and 87.5% improvement in abnormal vaginal discharge and cervical abnormalities. Microbiological cure rate found was 100% for pathogens. A constant decline was seen in the mean values of all the associated symptoms. Significant results in whiff and pH test were observed after treatment. The vaginal discharge was observed to be clear in 100% of the participants. Subject’s assessment of symptoms which were low back pain, vulval itching, general weakness, foul discharge, and burning sensation were improved. All results were significant at p value <0.05. The study found that BC caps is highly effective and safe in a treatment for abnormal vaginal discharge. It also showed improvements on associated symptoms with minimal to zero side effects.